Art and science: an interdisciplinary approach - Karow, Kim (My University, 2006)
Artist’s Statement: The work represented in this show was created over an eleven-year time span. The content within the pieces reflect upon three unrelated autobiographical events or themes but there are two points of view, sometimes happening simultaneously: the point of view of the scientist shown in image selection, and the feminine point of view seen in image execution. The hand of the woman artist is seen tending both the image and the subject within, metaphorically evident in the soft sheen of silk, hand sewn stitches. On the surface, disengagement (the perspective of the scientist) seems at odds with the role of the artist. Taking a deeper look at the pieces here, I think the audience will find that these works go beyond illustration to make connections about processes: biological, ecological and sometimes even emotional ones. However, I must admit I am not formally trained in the sciences, merely an observant artist who took the time to research a subject before commenting on it visually. For the viewer trained in aesthetics, you will find silverpoint and graphite drawings that attempt exactingly accurate representations of their subjects, rich with soft value gradations, texture, and implied motion. Graphic relief prints are filled with rhythmic patterns and bold linear qualities always mindful of fields of value breaking up the space. For the viewer trained in the biological sciences, you will find an artist who took the time to get it right. It encompasses the point of view of the physician using radiographic images, dissections and sutures. The point of view of the ecologist is seen in representations of interrelationships of an ecosystem dependent on soil, hydrology, host plants and companion plants. Surely the botanist will appreciate the lateral striations in the leaf of a rush usually only noticed under a microscope. However, if representational accuracy were the singular goal of this work, they would be high quality illustrations. My desire is that these images go beyond documenting the subject and show an interpretation by the artist to describe unseen processes: the process of illness, injury,birth, fire, relationships in nature and the struggle to understand it all at a deeper level. Perhaps Allen Carlson describes the duality of this show best: “If to appropriately aesthetically appreciate art we must have knowledge of art forms, classifications of works, and artistic traditions, then to appropriately aesthetically appreciate nature we must have knowledge of different natural environments and of the different systems and elements within those environments. As the knowledge provided by art critics and art historians equips us to aesthetically appreciate art, that provided by naturalists, ecologist, geologists, and natural historians equip us to aesthetically appreciate nature.” --“Aesthetic Appreciation and the Natural Environment” (1988)
This file last viewed in Adobe Reader 7.0
Keywords: Art and science -- Exhibitions.